Climatological Study of Urban Climate and Heat and Cold Mortalities in Japan - Fujibe, Fumiaki (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book describes observed features of urban climate and its long-term variations as well as the relationship of climate to heat stroke in Japan, based on observational data and statistical analyses. Consisting of three parts, the book is a valuable resource for researchers and professionals involved with these topics. Part 1 focuses on urban climate. The basic characteristics of heat islands are reviewed, and long-term urban warming is described with a focus on the distinction from global warming. The influence of microscale environmental changes on the observed temperature is also presented, as well as changes in wind and precipitation in urban areas. They deepen our understanding of the features and mechanisms of urban heat islands and their long-term changes. Part 2 describes the climatological features of heat stroke mortality, which has become a major social problem in Japan, using mortality statistics and meteorological data. The spatial and temporal variations of heat stroke mortality are analyzed quantitatively on various spatial and temporal scales. In addition, the number of ambulance transports is examined as another measure of heat stroke casualty. The results provide insight into the climatological factors related to heat stroke mortality and contribute to the implementation of preventive measures. The climatology of deaths from extreme cold is also presented. For supplementary information, an overview of the geography, climate, and meteorological data of Japan is presented in Part 3.
Part 1. Urban Heat Islands and Urban Warming in Japan -- Chapter 1. Basic Features of the Urban Heat Island (UHI) -- 1.1 Observational Studies on Nighttime UHIs -- 1.1.1 Examples of UHI -- 1.1.2 Vertical Structure of UHI -- 1.2 Climatology of UHI Intensity -- 1.2.1 Indices of UHI Intensity and Urbanness -- 1.2.2 Relationship between Nighttime UHI Intensity and Climatological Factors -- 1.3 Mechanisms of UHI Formation -- Chapter 2. Climatology of Long-term Urban Warming -- 2.1 Interest in Urban Warming -- 2.2 Detection of Urban Warming in Long-term Temperature Trends in Japan -- 2.2.1 Relationship between Temperature Trends and Population Density -- 2.2.2 Dependence of Temperature Trends on Population Density: Analysis for a Centennial Time Scale -- 2.3 Dependence of Urban Warming on Weather Conditions -- Chapter 3. Sub-city Scale Temperature Distribution -- 3.1 Introduction -- 3.2 Temperature around Urban Parks -- 3.3 Microscale Effects on Observed Temperature -- 3.4 Microscale Effects on Long-term Temperature Trends -- Chapter 4. Wind and Precipitation in Cities -- 4.1 Urban Wind -- 4.1.1 Urban Effects on Surface Wind Speed -- 4.1.2 Heat-island Circulation -- 4.1.3 Interaction between the Heat-island Circulation and Local Winds -- 4.2 Urban Humidity and Precipitation -- 4.2.1 Relative Humidity and Amount of Water Vapor -- 4.2.2 Urban Fog -- 4.2.3 Clouds and Precipitation in Cities -- 4.2.4 Urban Snow -- Part 2. Climatology of Heat and Cold Mortalities in Japan -- Chapter 5. Climatology of Heat Stroke Mortality in Japan -- 5.1 Basic Statistics of Heat Stroke Deaths in Japan -- 5.1.1 Outline of Heat Stroke Data -- 5.1.2 Definition of Heat Stroke Mortality Rate -- 5.1.3 Basic Statistics of Heat Stroke Mortality in Japan -- 5.2 Regional Variations of Heat Stroke Mortality Rates and Temperature -- 5.2.1 Outline of the Analysis Procedure -- 5.2.2 Spatial Patterns -- 5.2.3 Interannual Variability -- 5.2.4 Seasonal Variations -- 5.2.5 Summary and Remarks -- 5.3 Relationship between Daily Heat Stroke Mortality and Temperature -- 5.3.1 Background -- 5.3.2 Regional and Temporal Features -- 5.3.3 Summary and Remarks -- 5.4 Dependence of Municipality-wise Heat Stroke Mortality Rate on Temperature and Economic States -- 5.4.1 Background -- 5.4.2 Data and Procedure of Analysis -- 5.4.3 Results of Correlation Analysis -- 5.4.4 Summary and Remarks -- Chapter 6. Comparison of Climatology of Ambulance Transport Rates and Mortality -- 6.1 Background -- 6.2 Data and Analysis -- 6.3 Regional, Interannual and Seasonal Variations of Transport Rate -- 6.4 Relationship between Daily Transport Rate and Meteorological Factors -- 6.5 Summary and Remarks -- Chapter 7. Climatology of Cold Mortality in Japan -- 7.1 Background -- 7.2 Data and Analysis -- 7.3 Basic Statistics of Cold Mortality -- 7.4 Regional and Temporal Features of Cold Mortality -- 7.5 Relationship between Daily Cold Mortality and Temperature. -- 7.6 Dependence on Municipality-wise Cold Mortality on Temperature and Annual Income -- 7.7 Summary and Remarks -- Part 3. Outline of the Climate and Meteorological Observations in Japan -- Chapter 8. Outline of the Geography and Climate of Japan -- 8.1 Topography and Local Government System of Japan -- 8.2. Climatology of Summer High Temperature in Japan -- 8.2.1 Overview of the Climate of Japan -- 8.2.2 Outline of Midsummer Weather -- 8.2.3 Thermally-induced Winds and Urban Heat Island in the Kanto Plain -- Chapter 9. Availability and Homogeneity of Meteorological Data in Japan -- 9.1 Meteorological Observation Systems in Japan -- 9.1.1 JMA Observatories -- 9.1.2 Automated Meteorological Data Acquisition System (AMeDAS) -- 9.1.3 Kunai Observation -- 9.1.4 Other Surface Observations -- 9.1.5 Upper-level Observation -- 9.2 Temporal Homogeneity of JMA Observation Data -- 9.2.1 Effect of Site Changes -- 9.2.2 Change in Observation Equipment -- 9.2.3 Change in Observation Time.
Keywords: Physical geography; Climatology; Geography; Bioclimatology; Physical Geography; Climate Sciences; Regional Geography; Climate Change Ecology